PATRIOTISME DALAM SYAIR BITAQAH HAWIYYAH KARYA MAHMUD DARWISY - Muhammad Sayyidul Arwan; Faizetul Ukhrawiyah (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
Poetry is a literary media that is very dense of meaning. Poetry is also a medium for conveying ideas of a poet to be conveyed to the reader. In this paper the author will convey the explanation of the meaning poem “Bit}a>qah Hawiyyah” by Mahmud Darwisy using the study of semiotics. In this paper the presentation uses qualitative methods by library research and uses Riffaterre's semiotic theory. The formulation of the problem in this paper is how the form of the unity of meaning structure in the poem “Bit}a>qah Hawiyyah” by Mahmud Darwisy using Riffaterre's semiotic study. The purpose of this study was to determine the form of the unity of meaning structure in the poem “Bit}a>qah Hawiyyah” by Mahmud Darwisy using Riffaterre's semiotic study. The result of this research is the form of the unity of meaning structure in the poem “Bit}a>qah Hawiyyah” by Mahmud Darwisy is Nationalism and Patriotism which manifests in pride, love and maintenance of identity, homeland and ownership.